Penerapan Teknik Data Mining Untuk Memprediksi Jumlah Penumpang Pesawat Pada Bandara Indonesia - Subandi, Anriestito Verdwiansyah R.; Gunawan, Hary; Supriyanto, Kiven Lorenza (Fakultas Komputer - Universitas Universal, 2021)
The purpose of this research is to predict how many plane passengers on the airport Soekarno Hatta and Ngurah Rai with the data obtained on 2017 - 2021. On this research, this study will compare the dataset that this study acquired before from BPS, to predict the amount of the passengers on airport Soekarno Hatta and Ngurah Rai, this study will be using a software called RStudio and try to execute with simple linear regression method. The information from prediction and research can be used or changed by anyperson of importance such as for promotion, advertisement, as well as the usage on RStudio.